Effect of W addition on microstructure and mechanical properties of Ni base dual two-phase intermetallic alloys. Issue 1760 (12th February 2015) - Edatsugi, Daisuke; Kaneno, Yasuyuki; Numakura, Hiroshi; Takasugi, Takayuki
ABSTRACT: The effect of W addition on microstructure and mechanical properties of Ni3 Al (L12 ) and Ni3 V (D022 ) two-phase intermetallic alloys has been investigated. W was added to the base alloy composition, Ni75 Al10 V12 Nb3 (at. %) in place of either Ni, Al or V. The W-added alloy ingots were heat-treated in vacuum at 1575 K for 5 h. The majority of W-added alloys showed a dual two-phase microstructures while the alloy in which 3 at. % W substituted for Ni exhibited the dual two-phase microstructure containing W solid solution dispersions. Vickers hardness was significantly enhanced by W addition, which is primarily due to solid-solution strengthening.